2018
DOI: 10.1177/1354816618797250
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pricing decisions by potential tourists under uncertainty: The effects of tourism advertising

Abstract: The aim of this study is to examine the advertising information learning processes of potential tourists and observe how potential tourists sequentially adjust their perceived reference prices and purchase intentions with different risk preferences and choices with respect to gains (the current price is lower than the consumer’s reference price) or losses (the current price is higher than the reference price). In this study, a Bayesian experiment was conducted to elicit reference prices in the presence of tour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 63 publications
(73 reference statements)
0
17
0
1
Order By: Relevance
“…It causes inconveniences for resident such as noise at night [24], and this also lead to deterioration of tourism destinations due to residents' resistance [14]. In addition, it could also result in the decrease of the attractiveness of tourism destinations as Smith and her colleagues revealed that perception of crowdedness during night tours is significantly related to the decline of the attractiveness of the destination [15,24].…”
Section: Night Tourismmentioning
confidence: 99%
See 2 more Smart Citations
“…It causes inconveniences for resident such as noise at night [24], and this also lead to deterioration of tourism destinations due to residents' resistance [14]. In addition, it could also result in the decrease of the attractiveness of tourism destinations as Smith and her colleagues revealed that perception of crowdedness during night tours is significantly related to the decline of the attractiveness of the destination [15,24].…”
Section: Night Tourismmentioning
confidence: 99%
“…In Korea, cultural assets which were previously only opened during the day due to management issues have now been opened at night. Night tourism focuses mainly on cultural assets and promotes aspects such as night views, night experience activities, night transportation, night performances, and interpretation [15]. However, when night tourism is active and more tourists enter a limited area, crowding impairs immersion to the destination [14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to prospect theory, this tendency is called the certainty effect and it contributes to risk aversion in choices involving sure gains and to risk seeking in choices involving sure losses” (Kahneman and Tversky 1979, p. 263). Oh (2003, p. 389) extends prospect theory to the hospitality industry by suggesting, “a hotel that is trusted by its customers for consistent quality, for example, is likely to be viewed more favorable a choice than its competitor that provides often higher, but inconsistent (or unpredictable) quality.” Prospect theory has also been applied in the tourism literature to investigate tourists’ risk perceptions in response to changes in price (Nicolau 2012; Petrick 2005; Song and Jiang 2019) and their risk perceptions associated with upgrading hotel rooms or seats on airlines (Masiero, Pan, and Heo 2016; Lindenmeier and Tscheulin 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Not only is there counterfactual thinking associated with service quality (Park and Jang 2018) but there can be counterfactual thinking and regret associated with choosing the wrong lodging property that underperforms on providing a unique experience that will be positively evaluated on social media. Song and Jiang (2019, p. 230) acknowledge that “the relevant parameters in the prospect theory model are not fixed but vary.” Expanding prospect theory beyond its past applications in tourism focused on service quality (Oh 2003) and price (Nicolau 2012; Petrick 2005; Song and Jiang 2019) provides a more complete picture of the consumer decision-making process and a holistic understanding of all the facets that contribute to tourists’ deciding where to stay when traveling.…”
Section: Literature Reviewmentioning
confidence: 99%